Cancer Immunology and Immuno-Oncology (Innate vs. Adaptive Cell Immunity) - Nezami, Nariman; Sanchez, Carlos J.; Moon, John; Shaikh, Jamil; Kokabi, Nima (Digestive Disease Interventions, 2020)
Tumorigenesis occurs due to both intrinsic cellular genetic changes and imbalances within the tumor microenvironment. This microenvironment is composed of a complex ecosystem of tumor cells, vasculature, extracellular matrix, stromal cells, and immune cells. With these cells, there is both immune activation and immune suppression that promote or inhibit tumor development. These interactions lead to a constant flux of remodeling within the tumor microenvironment that additionally promote or inhibits tumor metastasis. To promote or suppress either antitumorigenic or protumorigenic effects, it is important to understand the complex interactions of the tumor and its interactions with the immune system within the tumor microenvironment. This review article addresses the role of the immune system and its cellular components within the tumor microenvironment.
Keywords: tumor; innate; adaptive; immune; lymphocyte; macrophage; dendritic cell; natural killer cell